The Phytochemical Screning and Assesment of Bioactivity of Pagoda Flower (Clerodendrum paniculatum L.) Using Brine Shrimp (Artemia salina) Lethality Assay - Hafiz, Ihsanul; Fitri, Khairani; Helvin, Sipayung Joi (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The purpose of this study was to determine the bioactive content of the pagoda flower ethanol extract and measure its activity using the brine shrimp lethal dose method Design: The design of this study was qualitative and quantitative experimental, where bioactive compounds of pagoda flower ethanol extract was tested by qualitatitive chemical analisys and brine shrimp lethal dose method was quantitatively calculated the number of deaths. Interventions: The variable that was intervened in this study was the concentration of extract used. Main outcome measurre: The main measurement results in this study were to know the bioactive compounds contained in the extract and the value of Lethality Concentration 50% (LC50). Results: The results of phytochemical screening from the ethanol extract of pagoda flowers showed bioactive compounds such as alkaloids, flavonoids, steroids/triterpenoids, tannins, saponins, and glycosides. The value of LC50 in the toxicity test for artemia salina was 49.415 ppm. Conclusion: The pagoda flower ethanol extract contains alkaloid compounds, flavonoids, steroids/triterpenoids, tannins, saponins, and glycosides. Pagoda flower ethanol extract has strong potential activity.